PERSonalised Incentives for Supporting Tobacco cessation (PERSIST) among healthcare employees: a randomised controlled trial protocol - Alex Burdorf; Jasper V Been; Frank J Van Lenthe; Nienke W Boderie; Johannes LW van Kippersluis; Diarmaid T Ó Ceallaigh; Márta K Radó (BMJ Open)
Background Smoking is the primary preventable risk factor for disease and premature mortality. It is highly addictive and cessation attempts are often unsuccessful. Incentive-based programmes may be an effective method to reach sustained abstinence. Individualisation of incentives based on personal characteristics yields potential to further increase the effectiveness of incentive-based programmes.Method A randomised controlled trial among healthcare workers recruited through their employer and signed up for a group-based smoking cessation programme. The intervention under study is the provision of personalised incentives on validated smoking cessation at several time points after the smoking cessation programme. A total of 220 participants are required. Participants are randomised 1:1 into intervention (personalised incentives) or control (no incentives). All participants join the group-based programme. Incentives are provided on validated abstinence directly after the smoking cessation programme and after 3, 6 and 12 months.Incentives are provided according to four schemes:(1) Standard: total reward size €350, pay-out scheme: €50 (t=0), €50 (t=3 months), €50 (t=6 months) and €200 (t=12 months), (2) descending: total reward size €300, pay-out scheme: €150, €100, €50 and €0, (3) ascending: total reward size: €400, pay-out scheme: €0, €0, €50 and €350 and (4) deposit: total reward size €450, pay-out scheme: €50, €50, €150, €200; participants pay a €100 deposit, returned conditional on abstinence after 6 months.Advice on which incentive scheme suits participants best is based on willingness to provide a deposit, readiness to quit, nicotine dependency and long-term or short-term reward preference. Participants are free to deviate from this advice. Abstinence is validated at each time point, with 15 months of total follow-up. The primary end point is validated abstinence at 12 months. Effectiveness will be determined by intention-to-treat analysis.Ethics and dissemination The Erasmus MC Medical Ethics Committee decided that according to the Dutch Human Research Law (WMO), the protocol required no formal ethical approval. The results will be published in a peer-reviewed scientific journal and communicated to the participants.Trial registration number Netherlands Trial Register NL7711.